Vitamin C Intake and Ischemic Stroke - Tang, Xiaolong; Liu, Hanguang; Xiao, Yuan; Wu, Lei; Shu, Peng (Frontiers in Nutrition, 2022)
Vitamin C is an essential micronutrient with important antioxidant properties. Ischemic stroke is a major public health challenge. Extensive evidence has demonstrated that vitamin C has protective effects in preventing cardiovascular disease (CVD), and there is a close relationship between vitamin C intake and ischemic stroke. Results from this umbrella review emphasize the relationship between vitamin C and ischemic stroke from four perspectives: cellular mechanisms, animal experiments, clinical trials, and cohort studies.